Characterization of High-polarization Stars and Blazars with DIPOL-1 at Sierra Nevada Observatory - Otero-Santos, J.; Piirola, V.; Escudero Pedrosa, J.; Agudo, I.; Morcuende, D.; Sota, A.; Casanova; V.; Aceituno, F. J.; Santos-Sanz, P. (Institute of Physics Publishing, 2025)
We report here the performance and first results of the new multiband optical polarimeter DIPOL-1, installed at the Sierra Nevada Observatory 90 cm T90 telescope (SNO, Granada, Spain). DIPOL-1 is equipped with a plane parallel calcite plate and λ/2 retarder for modulating the intensity of two perpendicularly polarized beams, and a high readout speed CMOS camera that allows for fast, time-dense coverage. We characterize the performance of this instrument through a series of tests on zero- and high-polarization standard stars. The instrumental polarization in the Nasmyth focus was well determined, with a very stable contribution of 4.0806% ± 0.0014% in the optical R band. For bright high-polarization standards (mR < 8) we reach precisions <0.02% in polarization degree and 01 in polarization angle for exposures of 2–4 min. The polarization properties of these stars have been constrained, providing more recent results also about possible variability for future studies of some of the most used calibrators. Moreover, we have tested the capability of observing much fainter objects, in particular through blazar observations, where we reach a precision of <0.5%−0.6% and <05 for faint targets (mR ∼ 16.5) with exposures of ∼1 hr. For brighter targets (mR ∼ 14.5−15), we can aim for time-dense observations with errors <0.2%−0.4% and <1°−15 in 5–20 min. We have successfully performed a first campaign with DIPOL-1, detecting significant polarized emission of several blazars, with special attention to the highest ever polarization degree measured from blazar 3C 345 at ∼32%.